2002
DOI: 10.1007/s00134-002-1412-5
|View full text |Cite
|
Sign up to set email alerts
|

Waiting for the break of dawn?

Abstract: Both late discharge and high discharge TISS scores are indicators of "premature" ICU discharge and were associated with increased mortality. Intermediate care reduced the mortality of patients discharged "prematurely" from ICU. This adds to the growing evidence of the benefits of intermediate care after ICU discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(39 citation statements)
references
References 20 publications
2
36
0
1
Order By: Relevance
“…Nine studies were excluded because they included data also reported in a larger study (i.e. large national database studies) [6, 13, 19, 2934]. Four studies were deemed ineligible on further review.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nine studies were excluded because they included data also reported in a larger study (i.e. large national database studies) [6, 13, 19, 2934]. Four studies were deemed ineligible on further review.…”
Section: Resultsmentioning
confidence: 99%
“…Differences in disease severity at admission to ICU have convincingly been shown not to explain the excess mortality and readmission rates found with out-of-hours discharge [1, 2, 8, 13, 15, 35]. The presence of treatment limitations at ICU admission also did not account for the effect [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While most studies define it as an unplanned admission to the ICU within 48 hours of discharge (3, 5, 6), definitons range from 3 to 30 days (4, 6, 26, 29). This may partly explain the discrepency in reported readmission rates, from 0.89% to 19% (1–5, 7, 9, 1316, 18, 22, 29). However, lower percentages do not necessarily infer better quality of care.…”
Section: Discussionmentioning
confidence: 98%
“…The authors suggested that this was in part because more ICU beds had been made available as lower-risk intensive monitoring patients were admitted to the IMCU so that high-risk patients who would otherwise have been managed on the general ward because of bed shortages were being more appropriately managed on the ICU. Beck and colleagues [12] reported that patients with high severity scores who were discharged to hospital wards had a higher risk of in-hospital death compared with patients discharged to a high-dependency unit, suggesting that the IMCU helped prevent ‘premature’ discharges to the ward. However, Campbell and colleagues [13] reported that discharge to a high-dependency unit was an independent risk factor for early ICU re-admission, suggesting that these patients had been discharged prematurely; importantly, as mentioned earlier, ICU readmission is associated with increased mortality rates [10].…”
Section: Intermediate Care Units: the Evidence For And Againstmentioning
confidence: 99%